TITIK TEMU DAN SINERGI EKONOMI ISLAM DAN EKONOMI KERAKYATAN - Sofyan Rizal (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2011)
In fact, Islamic and populist economy have the same objective: they are welfare and fairness for all people. In Islam, the economical welfare and the fairness must be based on Islamic norms and ethics. Koperasi is a populist economic institution that has been long existed in Indonesia. Koperasi is the main institution that is expected by the founders of this nation as a tool of economical equality and fairness. At the concept of implementation level, koperasi has a lot of compatybility with the appropiate institutions of economic empowerment of IslamDOI: 10.15408/aiq.v3i1.2493